2008
DOI: 10.1128/aac.01164-07
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Deletion of the Methicillin Resistance Determinant, mecA , Partially Compensates for the Fitness Cost Associated with High-Level Vancomycin Resistance in Staphylococcus aureus

Abstract: Treatment of infections caused byStaphylococcus aureus is often confounded by the bacterium's ability to develop resistance to chemotherapeutic agents. Methicillin-resistant S. aureus (MRSA) arises through the acquisition of staphylococcal chromosomal cassette mec (SCCmec), a genomic island containing the methicillin resistance determinant, mecA. In contrast, resistance to vancomycin can result from exposure to the drug, a mechanism that is not dependent upon a gene acquisition event. Here we describe three MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 43 publications
2
53
1
Order By: Relevance
“…Previous studies have shown that the relative fitness of hospital-acquired MRSAs carrying the type I SCCmec element is reduced (Ender et al, 2004), whereas strains containing the smaller type IV element were not affected (Lee et al, 2007). It has also been shown in vancomycin-resistant MRSA strains containing the type II SCCmec element that deletion of mecA compensated for some of the fitness costs associated with becoming vancomycin resistant, suggesting that mecA is also costly (Noto et al, 2008). A detailed study of the costs associated with all five classes of SCCmec elements and whether these costs have been compensated in clinical strains has not been performed to date.…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies have shown that the relative fitness of hospital-acquired MRSAs carrying the type I SCCmec element is reduced (Ender et al, 2004), whereas strains containing the smaller type IV element were not affected (Lee et al, 2007). It has also been shown in vancomycin-resistant MRSA strains containing the type II SCCmec element that deletion of mecA compensated for some of the fitness costs associated with becoming vancomycin resistant, suggesting that mecA is also costly (Noto et al, 2008). A detailed study of the costs associated with all five classes of SCCmec elements and whether these costs have been compensated in clinical strains has not been performed to date.…”
Section: Introductionmentioning
confidence: 93%
“…This observation suggests a fitness cost that may be associated with the presence of the mecA gene. A similar observation has been made in studies on S. aureus, where isolates lacking the mecA gene are able to outcompete their mecA-containing counterparts (Noto et al, 2008). However, this observation was made on only a single strain and therefore needs to be confirmed using a panel of similar strains.…”
Section: Discussionmentioning
confidence: 75%
“…Spontaneous excision of mecA, causing MSSA to emerge from MRSA both in vivo and in vitro, has been described in several other studies [138][139][140]. This phenomenon may be due to stressful conditions in vitro, such as long-term storage in antibiotic-free medium, nutrient starvation, elevated temperatures or UV radiation [138,[141][142].…”
Section: Paper IImentioning
confidence: 97%
“…This phenomenon may be due to stressful conditions in vitro, such as long-term storage in antibiotic-free medium, nutrient starvation, elevated temperatures or UV radiation [138,[141][142]. Furthermore, prolonged therapy with non-β-lactam antibiotics and exposure to vancomycin can be contributing factors, resulting in partial excision of SCCmec [140].…”
Section: Paper IImentioning
confidence: 99%